Dekomunizacja zielonogórskich urbanonimów - Żuraszek-Ryś, Iwona (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The article describes the process of decommunization of urbanonyms in one of the Polish voivodeship capitals, Zielona Góra. It presents both the changes in naming we are witnessing currently and past ones. During the first removal of communist patrons we still had to deal with the period of the Polish People’s Republic after Stalin’s death and Władysław Gomułka’s coming to power. However, the changes introduced at that time were quite limited and concerned a small number of people who were no longer in power – Stalin and Marshal Rola-Żymierski. The proper decommunization was related to the political transformation after 1989. The previous urbanonyms, based mainly on anthroponyms, were replaced with names referring to people and events that could not be commemorated before and were to be erased from history (e.g. ul. Hanki Sawickiej changed to ul. gen. Okulickiego). In addition, the changes were motivated by the need nto commemorate local activists and heroes, and to highlight the history and topography of the city. The last decommunization was enforced by the enactment of the Act on the Prohibition of Propagation of Communism or Other Totalitarian Regimes and ended quite recently (the last street name change was voted on on March 27, 2018). Four streets in Zielona Góra have been renamed, including two referring to military organizations associated with the communist movement (ul. Armii Ludowej→ ul. Władysława Jagiełły and ul. II Armii → ul. Żołnierzy 2 Armii), and two based on dates (ul. Przylep-22 Lipca → ul. Przylep-Solidarności and ul. Przylep-9 Maja → ul. Przylep-8 Maja). Therefore, in the case of both decommunizations, ideological considerations prevailed, and to a lesser degree so did economic or cultural ones.